Antitumoral Potential of Artepillin C, a Compound Derived from Brazilian Propolis, against Breast Cancer Cell Lines - de Freitas Meirelles, Lyvia E.; de Assis Carvalho, Analine R. B.; Ferreira Damke, Gabrielle Marconi Zago; Souza, Raquel Pantarotto; Damke, Edilson; de Souza Bonfim-Mendonça, Patrícia; de Oliveira Dembogurski, Djaceli Sampaio; da Silva, Denise Brentan; Consolaro, Marcia Edilaine Lopes; da Silva, Vânia Ramos Sela (Anti-Cancer Agents in Medicinal Chemistry, 2024)
Background: Breast cancer is the most commonly diagnosed cancer among women worldwide with limited treatment options. Artepillin C (3,5-diprenyl-4-hydroxycinnamic acid) is one of the main constituents of Brazilian propolis presenting different activities, including antitumoral effects against various types of cancer. Objective: We evaluated the antitumoral potential and mechanisms of action of artepillin C against two distinct human breast cancer cell lines, MCF-7 and MDA-MB-231, to explore a new therapeutic candidate. Methods: Cell viability was assessed by MTT assay and the long-term cytotoxicity was performed by clonogenic assay. The morphological changes were observed by light microscopy, analysis of cell death pathway by Annexin V FITC/propidium iodide (PI), lactate dehydrogenase (LDH) by colorimetry, DNA fragmentation by agarose gel and senescence by β-galactosidase. Detection of total reactive oxygen species (ROS) by fluorescence microscopy and determination of mitochondrial transmembrane potential by flow cytometry were also performed. Results: Artepillin C presented a strong and dose-time-dependent cytotoxic effect on MCF-7 and MDA-MB-231 cell lines, with cytotoxicity more evident in MCF-7. In both cancer cell lines, the clonogenic potential was significantly reduced and the morphology of the cells was changed. The treatment also induced death by necrosis and late apoptosis in MCF-7 and MDA-MB-231 and induced cell senescence in MCF-7. Also, artepillin C increased total ROS in both cancer cells and decreased mitochondrial membrane potential in MDA-MB-231 cells. Conclusion: Artepillin C presented antitumoral potential in two human breast cancer cell lines, MCF-7, and MDA-MB-231, suggesting a new promising option for the treatment and/or chemopreventive strategy for breast cancer.
Keywords: propolis